Outbreak of Zika Virus Infection, Chiapas State, Mexico, 2015, and First Confirmed Transmission by Aedes aegypti Mosquitoes in the Americas. (19th July 2016) - Guerbois, Mathilde; Fernandez-Salas, Ildefonso; Azar, Sasha R.; Danis-Lozano, Rogelio; Alpuche-Aranda, Celia M.; Leal, Grace; Garcia-Malo, Iliana R.; Diaz-Gonzalez, Esteban E.; Casas-Martinez, Mauricio; Rossi, Shannan L.; Del Río-Galván, Samanta L.; Sanchez-Casas, Rosa M.; et al.
Abstract: Background.  After decades of obscurity, Zika virus (ZIKV) has spread through the Americas since 2015 accompanied by congenital microcephaly and Guillain-Barré syndrome. Although these epidemics presumably involve transmission by Aedes aegypti, no direct evidence of vector involvement has been reported, prompting speculation that other mosquitoes such as Culex quinquefasciatus could be involved. Methods.  We detected an outbreak of ZIKV infection in southern Mexico in late 2015. Sera from suspected ZIKV-infected patients were analyzed for viral RNA and antibodies. Mosquitoes were collected in and around patient homes and tested for ZIKV. Results.  Of 119 suspected ZIKV-infected patients, 25 (21%) were confirmed by RT-PCR of serum collected 1–8 days after the onset of signs and symptoms including rash, arthralgia, headache, pruritus, myalgia, and fever. Of 796 mosquitoes collected, A. aegypti yielded ZIKV detection by RT-PCR in 15 of 55 pools (27.3%). No ZIKV was detected in C. quinquefasciatus . ZIKV sequences derived from sera and mosquitoes showed a monophyletic relationship suggestive of a point source introduction from Guatemala. Conclusions.  These results demonstrate the continued, rapid northward progression of ZIKV into North America with typically mild disease manifestations, and implicate A. aegypti for the first time as a principal vector in North America.